Some Questions and Answers About the Role of Hox Temporal Collinearity in Vertebrate Axial Patterning - Durston, Antony J. (Frontiers in Cell and Developmental Biology, 2019)
Abstract The vertebrate anterior-posterior (A-P = craniocaudal) axis is evidently made by a timing mechanism. Evidence has accumulated that tentatively identifies the A-P timer as being or involving Hox temporal collinearity. Here, I focus on the two current competing models based on this premise. Common features and points of dissent are examined and a common model is distilled from what remains. This is an attempt to make sense of the literature.